Biochemical and biomedical studies on African walnut (Tetracarpidium conophorum -Mull. Arg.) – a postharvest perspective - Nkwonta, Chikere Godwin (Cranfield University, 2015)
African Walnut (Tetracarpidium conophorum- Mull. Arg) is a perennial climbing shrub which grows mainly in the Western region of Africa. It is found mainly in Nigeria, Gambia, Sierra Leone, Gabon, Equatorial Guinea and Cameroon as well. The nuts are encased in pods which may contain between 2 to 5 nuts. The seed is enclosed in a hard shell-like case. The nuts are commonly processed by boiling or roasting and consumed as a snack or used as soup thickener. In ethnobotanical medicine, the nut extract is extensively used in decoctions for treatment and/or management of common and chronic ailments such as malaria, dysentery, high blood pressure, diabetes and cancer. The nuts are generally exposed to high temperatures (25 – 37 °C) and relative humidity (RH) which increases susceptibility to fungal contamination and nutrient degradation, hence, raising concerns over product quality and safety. Experiment simulating the common retail postharvest storage and processing practices was conducted to: (i) determine the effects on the fatty acid profile; (ii) assess the impact on the fungal population contaminating the nut shells at different maturity stages, and potential mycotoxigenic implications; (iii) evaluate the cytotoxicity of four extract of the nut on lung cancer (A549) cells; and finally (iv) assay the total phenolic content and profile potential individual phenolic components of the nut. Results indicated the presence of essential and non-essential fatty acids namely; palmitate, oleate, stearate, linoleate, arachidate and α-linolineate with α-linolineate being the most abundant (1.1 – 8.2 mg/g freeze-dry weight). Boiling and roasting generally improved the concentration of the fatty acids best when nuts are cold stored at 5 °C for maximum of 10 days. Potential mycotoxigenic species - Aspergillus section Nigri, Aspergillus flavus/Parasiticus, Fusarium spp. and Penicillium spp. - were frequently isolated from cultured shell pieces of stored nuts. When compared with unprocessed nuts, roasting completely prevented fungal contamination in shell pieces from nuts in the non-stored (NSN) group at early maturity stage, while boiling significantly reduced the level of contamination to about 58 % (P < 0.05). Simulating open market conditions caused 100% fungal contamination in all boiled samples and roasted samples at early maturity. Mycotoxin analysis using Yeast Extract agar (YES) and High Performance Liquid Chromatography (HPLC) - Fluorescence detector (FLD) showed that Aflatoxins - G1 (AFG1), B1 (AFB1), G2 (AFG2), and B2 (AFB2) were produced by 20 isolates with both AFG1 and AFB1 being predominant at concentration ranges 4 – 32,200 and 4 – 22,700 ng/g plug weight, respectively. No Ochratoxin A (OTA) was detected. Phenolic component analysis indicated unprocessed (20.79 ± 1.0 mg gallic acid equivalent per gram freeze-dry weight – GAE/g FDW) samples showed the highest value for total phenolics while both boiling (9.90 ± 1.8 mg GAE/g FDW), and roasting (9.32 ± 2.7 mg GAE/g FDW) reduced the amount by more than 50 % when compared with unprocessed. Potential individual phenolic compounds were unambiguously separated using high performance liquid chromatography – diode array detector (HPLC-DAD). There were no differences between chromatograms of defatted and non-defatted unprocessed, roasted and boiled samples. Cytotoxicity evaluation showed no decrease in cell densities in plates treated with extracts from unprocessed nuts at all concentrations. Diethyl ether-ethyl acetate (10 µg/mL) and n-butanol (1000 and 500 µg/mL) extracts of roasted nuts as well as dichloromethane and water (1, 10 µg/mL) of boiled nuts caused a non-significant decrease of < 10 % in cell densities when compared with the phosphate buffered saline-media control. However, all extracts showed no cytotoxic effect on the A549 cells African walnut is basically produced at subsistence level in Nigeria, but considering the presence of desirable fatty acid profile and phenolic compounds, need for increased industrial scale production is herein recommended. Although fungal attack and potential mycotoxin risk on the nut may be high, retail processing by roasting has prospects to greatly accentuate the risk. Cold storage of the nut may help to improve the shelf life although it may not be cost effective for local farmers in Nigeria and Africa, however, it provides opportunity for export business. Although the nut extracts showed no cytotoxic effect on A549 lung cancer cell lines, there is need to investigate further to confirm it non-cytotoxicity activity on other cancer lines and normal cell lines.